3-(Triflyloxy)benzynes Enable the Regiocontrolled Cycloaddition of Cyclic Ureas to Synthesize 1,4-Benzodiazepine Derivatives - Kaneko, Hideki; Ikawa, Takashi; Yamamoto, Yuta; Arulmozhiraja, Sundaram; Tokiwa, Hiroaki; Akai, Shuji (Synlett, 2018)
A versatile synthesis of 1,4-benzodiazepine derivatives through the reaction of various 3-(trifluoromethanesulfonyloxy)benzynes with N-(p-toluenesulfonyl)imidazolidin-2-ones is reported. This reaction system provides a 1,4-benzodiazepine bearing a trifluoromethanesulfonyloxy group as a single regioisomer among the four possible regioisomers.
Keywords: benzodiazepines; benzynes; triflyloxy group; imidazolidinones; regioselectivity; directing group